Ditadura e educação: currículo e estudos sociais na Escola Polivalente (Alagoinhas/BA) e na Escola de 1° e 2° graus Prof. Abelardo Romero Dantas (Lagarto/SE), 1968-1980 - Nascimento, Grasiele Ferreira do (2023)
The 1st and 2nd grade educational reforms were some of the processes responsible for foreign policy, and in the negotiations for the entry of foreign capital into the country through international capital into the country through international agreements, such as those signed between the Ministry of Education and Culture (MEC) and the United States Agency for International Development (Usaid), which contributed to the government's propaganda backed by the defense of professional education. However, in reaction, there were movements organized by student bodies and teachers' associations. teachers' associations. This paper is dedicated to analyzing the educational educational policies of the 1960s and 1970s, in order to understand the structuring of the power instruments of the military state, which was markedly centralizing and ideological. It questions and reflects on the political interference in pedagogical movements, especially those especially those that advocated humanized education. The government's government proposals in the field of education have altered the layout and organization of history teaching, especially in History, especially in basic education, with the introduction of Social Studies, as compulsory in the primary school curriculum, to the detriment of the History and Geography subjects separately. Geography separately, leading to the emptying out of the contents of the human Sciences. This research aims to investigate how the humanities curriculum was organization of the humanities curriculum with Law No. 5,692 of August 11, 1971, and Parecer 853, of November 11, 1971, and how they were applied in the states of Bahia and Sergipe. states of Bahia and Sergipe, choosing two educational institutions with strong popular respect, the Escola Polivalente de Alagoinhas (BA) and the Escola de 1.º e 2.º graus Prof. Abelardo Romero Dantas (Lagarto/SE). The use of official documents, such as national laws and decrees documents produced by the school secretariats and by the teachers themselves, such as class themselves, such as class diaries and minutes of meetings, correspondence sent by the State Education Council and photographs were important historical sources for the results of this research. Through comparative history and qualitative through comparative history and qualitative analysis, despite their different trajectories and teaching projects, we sought to establish the two educational realities, in an authoritarian politicaleconomic-social-cultural context that is highly complex for the for understanding social relations in the school environment.